Comparison of Prognosis and Lymph Node Metastasis in T1-Stage Colonic and Rectal Carcinoma: A Retrospective Study - Deng J; Zhou S; Wang Z; Huang G; Zeng J; Li X (International Journal of General Medicine, 2022)
Jun Deng, Shifa Zhou, Zhiwen Wang, Genbo Huang, Jingjun Zeng, Xiujiang Li Department of Emergency Surgery, The First Affiliated Hospital of Nanchang University, Nanchang, People’s Republic of ChinaCorrespondence: Xiujiang Li, Department of Emergency Surgery, The First Affiliated Hospital of Nanchang University, Nanchang, 17 Yongwaizheng Street, Nanchang, 330006, Jiangxi, People’s Republic of China, Tel/Fax +86-791-8869-2540, Email xiujiang_li@email.ncu.edu.cnBackground: Limited evidence and contradictory results have been reported regarding the impact of tumor site on lymph node metastasis (LNM) and prognosis in T1 stage adenocarcinoma (AC). We aimed to compare two anatomic locations in terms of LNM and prognosis using a comprehensive statistical analysis of a large population.Methods: The Surveillance, Epidemiology, and End Results (SEER) database and our center (First Affiliated Hospital of Nanchang University) were used to extract patient information. Univariate and multivariate logistic or Cox regression and propensity score matching were used to explore the association between LNM/survival and tumor site.Results: Information for 12,404 patients, including 9655 colonic AC and 2749 rectal AC patients, was extracted from the SEER database. The 516 AC patients included 184 colonic and 332 rectal AC patients from our center. Multivariate logistic regression analysis revealed a correlation between LNM and tumor site (colon vs rectum, odds ratio [OR] =1.52, 95% CI, 1.349– 1.714, P< 0.001). Additionally, we found that younger age, T1b stage, poor differentiation, and lymphatic invasion were risk factors for LNM. After adjusting for confounding factors by PSM, we found that the location of the rectum remained a higher risk factor for LNM. However, we found that patients diagnosed with rectal AC had a prognosis similar to that of patients diagnosed with colonic AC, which was demonstrated by the analysis of SEER data and data from our center.Conclusion: T1-stage rectal AC may have a higher risk of LNM than colonic AC, while rectal AC has a prognosis similar to that of colonic AC.Keywords: colorectal adenocarcinoma, anatomic location, SEER, lymph node metastasis, survival